Coexistence of Rheumatoid Arthritis, Systemic Lupus Erythematosus, Sjogren Syndrome, Antiphospholipid Syndrome, and Ankylosing Spondylitis - Khasru, Moshiur Rahman; Siddiq, Md Abu Bakar; Sayeeduzzaman, Kazi Mohammad; Marzen, Tangila; Salek, Abul Khair Mohammad (Case Reports in Rheumatology, 2021)
A 37-year-old Bangladeshi woman presented with low back and several joints pain and swelling for months together; there was significant morning stiffness for more than two hours. Repeated abortions, dry eye, hair fall, photosensitivity, and oral ulcer were the additional complaints. Clinical examination unveiled asymmetrical peripheral and both sacroiliac joint tenderness, positive modified Schober’s test, and limited chest expansion. Schirmer’s test was positive. The history of rheumatoid arthritis (RA) and ankylosing spondylitis (AS) among 1st-degree relatives was also significant. Biochemical analysis revealed pancytopenia, raised erythrocyte sedimentation rate (ESR) and C-reactive protein (CRP), and mild microscopic proteinuria. The patient was seropositive for rheumatoid factor (RF), antibodies against cyclic citrullinated peptides (anti-CCP), antinuclear antibody (ANA), anti-Sm antibody, anti-Sjögren’s-syndrome-related antigen A and B (anti-SSA/SSB), antiphospholipid (aPL-IgG/IgM), and HLA B27; however, serum complement (C3 and C4) levels were normal. Basal cortisol level measured elevated. Besides, X-ray and MRI of lumbosacral spines demonstrated sacroiliitis. There was radiological cardiomegaly, echocardiography unveiled atrial regurgitation, and ascending aorta aneurysm. Based on the abovementioned information, RA, AS, and systemic lupus erythematosus (SLE) have been diagnosed. Moreover, the patient developed Sjogren’s syndrome (SS), antiphospholipid lipid syndrome (APS), Cushing syndrome, ascending aorta aneurysm, and atrial regurgitation. Her disease activity score for RA (DAS28), DAS for AS (ASDAS), SLE disease activity index (SLEDAI), and Systemic Lupus International Collaborating Clinics/American College of Rheumatology (SLICC/ACR) scores were 3.46, 2.36, 23, and 5, respectively. The patient received hydroxychloroquine (200 mg daily), pulsed cyclophosphamide, prednisolone (20 mg in the morning), and naproxen 500 mg (twice daily). To our best knowledge, this is the first report documenting RA, AS, and SLE with secondary SS and APS.